2008
DOI: 10.1021/ja806475k
|View full text |Cite
|
Sign up to set email alerts
|

Protein Side-Chain Dynamics and Residual Conformational Entropy

Abstract: Changes in residual conformational entropy of proteins can be significant components of the thermodynamics of folding and binding. Nuclear magnetic resonance (NMR) spin relaxation is the only experimental technique capable of probing local protein entropy, by inference from local internal conformational dynamics. To assess the validity of this approach, the picosecond-to-nanosecond dynamics of the arginine side-chain Nε-Hε bond vectors of E. coli ribonuclease H (RNase H) were determined by NMR spin relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
129
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 59 publications
12
129
0
Order By: Relevance
“…S8), consistent with other studies (40). Conformational heterogeneity appears in the SC of a highly buried Arg while still maintaining ordered contacts (41). These and other examples illustrate that upon folding, surface and core residues lose an amount of entropy that depends on context.…”
Section: Resultssupporting
confidence: 89%
“…S8), consistent with other studies (40). Conformational heterogeneity appears in the SC of a highly buried Arg while still maintaining ordered contacts (41). These and other examples illustrate that upon folding, surface and core residues lose an amount of entropy that depends on context.…”
Section: Resultssupporting
confidence: 89%
“…16,17,19,20 Therefore, MD simulations are often used to supplement the NMR measurements to provide the total conformational entropy of the protein. 16,21,22,23,24,25,26,27,28,29 Protein conformational entropies are the main topic of this study, but it should be remembered that there are other important contributions to the total entropy as well, e.g. from the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The conformational entropy of the simulated proteins has been calculated with four different methods. In the first, which we will denote dihedral-distribution histogramming (DDH), 24,55 the protein Cartesian coordinates were converted to internal (bond, angle, and torsion) coordinates. Previous calculations have shown that entropy contributions from the bond and angle fluctuations are negligible.…”
mentioning
confidence: 99%
“…The 15 N ϵ ‐ 1 H ϵ order parameter is not sensitive to all arginine side‐chain motions, since there exist multiple conformations of the side‐chain that have a similar orientation of the H ϵ −N ϵ bond vector 16. However, although a strict relationship between the order parameter and conformational entropy is not available, important information about conformational entropy can be obtained from the order parameters.…”
mentioning
confidence: 99%
“…[17] Shown are 80 000 randomly selected data points out of the totally 8×10 6 obtained. Included as black points are the correlations obtained previously from MD simulations of RNaseH16 (see Supporting Information). b) Histogram showing the distribution of conformational entropies for an order parameter of 0.46< S 2 <0.48. c) Histogram showing the distribution of conformational entropies for an order parameter of 0.89< S 2 <0.91.…”
mentioning
confidence: 99%